Differences in pragmatic communication skills of adults with intellectual disabilities and dual diagnoses - Djordjevic, Mirjana; Glumbić, Nenad; Brojčin, Branislav; Banković, Slobodan; Žunić Pavlović, Vesna (Frontiers in Psychiatry, 2023)
Pragmatics includes a set of skills related to language structure and meaning that allow the speaker to use the language appropriately and in accordance with different communication situations. The aim of this research was to determine the differences in pragmatic communication skills of adults with intellectual disabilities, dual diagnoses, and typical development, and to determine the effects of gender, age, the level of intellectual functioning and speech comprehension on their achievements on two assessment instruments. The sample included 180 adults (60 typically developing participants, 60 with intellectual disabilities, and 60 participants with dual diagnoses). We used two instruments to assess pragmatic communication skills – Communication Checklist – Adult, CC-A, and The Assessment Battery for Communication, ABaCo. In order to test the differences between the three groups of participants, we used canonical discriminant analysis. Discriminant analysis revealed two significant canonical functions. Function one (speech comprehension and the level of intellectual disability, social engagement and paralinguistic scale) differentiates between typically developing participants and participants with dual diagnoses the most. The second canonical function (language structure, linguistic scale, paralinguistic scale, extralinguistic scale and context scale) differentiates between participants with intellectual disabilities and participants with dual diagnoses the most. According to the results, age did not affect pragmatic achievements.